EARLY ENGLISH PRINTING AND THE HANDS OF COMPOSITORS - Tokunaga, Satoko (International Journal of English Studies, 2009)
This paper examines soine distinctive uses of typefaces by Caxton's compositors in his early products at Westminster and illustrates how useful such examples are in revealing the chronology of actual book production, as well as in identifying the compositors at work on individual volumes. An exhaustive analysis of early printed books can provide us with information about compositors at work in England's earliest printing house. This paper therefore argues that it is inost definitely worth considering such 'inechaiiical' aspects of book design as typography when editing any printed text, and introduces most recent research results contributed by a project at Keio University, which airns to establish a semiautomatic system that can transcribe every feature of the printed text including even minute differences in types.